Enhancing access to alcohol use disorder pharmacotherapy and treatment in primary care settings: ADaPT-PC. (December 2015) - Hagedorn, Hildi; Brown, Randall; Dawes, Michael; Dieperink, Eric; Myrick, Donald; Oliva, Elizabeth; Wagner, Todd; Wisdom, Jennifer; Harris, Alex
Abstract Background Only 7.8 % of individuals meeting diagnostic criteria for alcohol use disorder (AUD) receive treatment in a given year. Most individuals with AUDs are identified in primary care (PC) settings and referred to substance use disorders (SUD) clinics; however, only a minority of those referred attend treatment services. Safe and effective pharmacological treatments for AUD exist, but they are rarely prescribed by PC providers. The objective of this study is to refine, implement, and evaluate an intervention to integrate pharmacological AUD treatment options into PC settings. This paper provides a detailed description of the intervention design and the evaluation components. Methods/design Three large Veterans Health Administration (VHA) facilities are participating in the intervention. The intervention targets stakeholder groups with tailored strategies based on implementation theory and prior research identifying barriers to implementation of AUD pharmacotherapy. Local SUD providers and primary care mental health integration (PCMHI) providers are trained to serve as local implementation/clinical champions and receive external facilitation. PC providers receive access to consultation from local and national clinical champions, educational materials, and a dashboard of patients with AUD on their caseloads for case identification. Veterans with AUD diagnoses receive educational information in the mail just prior to a scheduled PC visit. Effectiveness of the intervention will be evaluated through an interrupted time series with matched controls to monitor change in facility level AUD pharmacotherapy prescribing rates. Following Stetler's four-phase formative evaluation (FE) strategy, FE methods include (1) developmental FE (pre-implementation interviews with champions, PC providers, and Veterans), (2) implementation-focused FE (tracking attendance at facilitation meetings, academic detailing efforts by local champions, and patient dashboard utilization), (3) progress-focused FE (tracking rates of AUD pharmacotherapy prescribing and rates of referral to PCMHI and SUD specialty care), and (4) interpretive FE (post-implementation interviews with champions and PC providers). Analysis of FE data will be guided by the Consolidated Framework for Implementation Research (CFIR). Discussion If demonstrated to be successful, this implementation strategy will provide a replicable, feasible, and relative low-cost method for integrating AUD treatment services into PC settings, thereby increasing access to AUD treatment.